Concept Analysis of Mindfulness Based on Islam Religion - Meidiana dwidiyanti; Reza Indra Wiguna; Akhmad Yanuar Fahmi Pamungkas; Hasanah Eka Wahyu Ningsih; Muhamad Ibnu Hasan (Jurnal Ilmu Keperawatan, 2018)
Mindfulness practice is one part of the holistic nursing has a concept that can be changed according to the needs, culture and customs of a society. It's been a lot of development of the concept of mindfulness which is adapted to the cornerstones of a religion like Buddhism, Christian and Hinduism however mindfulness based on Islam religion still very lack of concept development. The aim of this study were to expand the understanding and clarify the concept of mindfulness based on Islam Religion. Walker and Avant’s concept analysis procedure was used as method in this concept analysis consisted of nine steps. A literature review was conducted using online database such as Proquest, PubMed, Science Direct, and EBSCO (MEDLINE CINAHL). Inclusion criteria included article written in English, with no limitation on publication date. The concept of mindfulness based on Islam Religion has a lack definitional identifying and clarification related to mindfulness for moslem people which often face confusion with how to apply mindfulness in accordance with the religion of Islam. Defining attributes to mindfulness based on Islam Religion were awareness, God and human relationship, and healing process. Antecedents to mindfulness based on Islam Religion included Islamic culture of praying characterized by God and human relationship derived from the strength of faith, shalat and belief to God. This review identified awareness, God and human relationship, and healing process as the defining attributes of Mindfulness based on Islam Religion. The closeness of relationship between God and human was expanded by implementing mindfulness with Islamic culture. Future research should explore the effect of mindfulness based on Islam Religion on psychiatric and mental disorder problems among moslem people especially Indonesian society.